3D-printed planar microfluidic device on oxyfluorinated PET-substrate. (July 2021) - Doronin, F.A.; Rudyak, Yu.V.; Rytikov, G.O.; Evdokimov, A.G.; Nazarov, V.G.
Abstract: The paper proposes the material extrusion additive manufacturing (via filament fabrication (FFF)) of planar microfluidics devices on the surface-modified PET-substrates production. The transformation of PET-substrates' morphological structure under the action of a multi-gas-phase modifying mixture significantly improves the wetting and the adhesion of the PLA-filament to them. A significant change in the chemical composition and nanorelief of PET substrates' surfaces as a result of processing with a gas mixture based on helium, nitrogen, fluorine and oxygen is confirmed experimentally by scanning electron microscopy (SEM), energy-dispersive spectroscopy (EDS) and fourie-transform infra-red spectroscopy (FTIR). The twelve-fold increase in the adhesion of the filament (measured) and the two-fold difference in the free surface energy values (calculated) for the original and the modified PET-substrates were observed. The functional characteristics' variances were accompanied with an approximately ten-fold increase in the degrees of heterogeneity for the carbon and oxygen concentration distributions and with the two-fold changes in the localization region and the average amplitude of the corresponding morphological spectra. The significant increase in the rate of mass transfer of an isotonic aqueous solution of sodium chloride through the surface microchannels of the constructed planar microfluidics device confirms the considerable changes in wettability of the modified PET substrates' surfaces. Highlights: A new technique for microfluidics devices manufacturing is proposed. The oxyfluorination improves the filament to PET-substrate adhesion by 12 times. The open microchannels transport characteristics are also increases. Simulation shows twofold rise in modified PET-surface nanotexture heterogeneity.